Just Java™ 2 - van der Linden, Peter (Java series (Mountain View, Calif.), 2004)
The #1 introduction to J2SE 1.5 and enterprise/server-side development! An international bestseller for eight years, Just Java™ 2 is the complete, accessible Java tutorial for working programmers at all levels. Fully updated and revised, this sixth edition is more than an engaging overview of Java 2 Standard Edition (J2SE 1.5) and its libraries: it's also a practical introduction to today's best enterprise and server-side programming techniques. Just Java™ 2, Sixth Edition, reflects both J2SE 1.5 and the latest Tomcat and servlet specifications. Extensive new coverage includes: New chapters on generics and enumerated types New coverage of Web services, with practical examples using Google and Amazon Web services Simplified interactive I/O with printf() Autoboxing and unboxing of primitive types Static imports, foreach loop construct, and other new language features Peter van der Linden delivers expert advice, clear explanations, and crisp sample programs throughout-including dozens new to this edition. Along the way, he introduces: The core language: syntax, objects, interfaces, nested classes, compiler secrets, and much more Key libraries: date and calendar, pattern matching, network software, mapped I/O, utilities and generic collections Server-side technology: network server systems, a complete tiny HTML Web server, and XML in Java Enterprise J2EE: Sql and JDBC™ tutorial, servlets and JSP and much more Client-side Java: fundamentals of JFC/Swing GUI development, new class data sharing details Companion Web Site All the book's examples and sample programs are available at http://afu.com.